Encouraging Literate Students to Embrace More Literacy Behaviors - El-Sulukiyyah, Ana Ahsana; Pusparini, Diah Anita (Mutiara Intelektual Indonesia Press, 2023)
Being literate is not merely able to read and write a language. Schools and classes are calling themselves as having a literacy program so as to facilitate their students with literacy behaviors. Hence, students are mostly literate only with the materials from school. They tend to read and act like literate students at school where the teachers are around. However, whether they are truly literate through other literacy behaviors is another question to ask and will be answered in this article. As seen that the purpose of this article is to know whether students considered themselves as literate students as well as to describe their literacy behaviors. It is stated earlier that literacy behaviors are not only related to reading and writing, whereas those will be stated more clearly in this article. The target respondents of this article to fulfill the data were the English Education Study Program students of Universitas PGRI Wiranegara. They were given an online questionnaire and answered several questions related to their knowledge and self-evaluation about literate and literacy behaviors. The result shows that they are aware of being literate students and, interestingly, they have various subjects and activities referred to literacy behaviors. Through realizing the students’ literacy behaviors, teachers/lecturers will be able to design certain materials and assignments which are in the area of students’ comfort as well as not neglecting the need for challenges.